Key drivers of village fund management accountability: Insights from Sukoharjo district - Khoirudin, Khoirudin; Noer Sasongko; Banu Witono (JIFA (Journal of Islamic Finance and Accounting), 2024)
This study investigates the impact of the government's internal control system, the village financial system application (Siskeudes), and the competence of village apparatus on the accountability of village fund management in Sukoharjo District. Utilizing a quantitative approach, data were collected from a sample of village apparatus using a simple random sampling technique. Respondents, who are operators of the Siskeudes application, provided insights through a structured questionnaire. The data were analyzed using multiple regression analysis. The findings reveal that both the government's internal control system and the Siskeudes application significantly enhance the accountability of village fund management. However, the competence of the village apparatus does not have a significant effect on accountability. These results suggest that robust internal controls and effective financial systems are critical for ensuring transparency and accountability in village fund management. The study contributes to the ongoing discourse on public fund management by highlighting the importance of technological and systemic factors over individual competencies in achieving accountable governance.